2008
DOI: 10.1292/jvms.70.1159
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibilities of Salmonella from Domestic Animals, Food and Human in the Mekong Delta, Vietnam

Abstract: ABSTRACT. A total of 230 Salmonella isolates representing 33 serotypes originated from food (pork, beef, chicken meat, duck meat, and shrimp), domestic animals (pig, chicken, and duck), and human (children with diarrhea) in the Mekong Delta, Vietnam were examined for the antimicrobial resistance to 10 antibiotics. Of the 230 Salmonella isolates examined, 49 (21.3%) showed antimicrobial resistance. Thirty-eight isolates (16.5%) were resistant to oxytetracycline, 26 (11.3%) to chloramphenicol, 17 (7.4%) to nalid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
(38 reference statements)
3
23
2
Order By: Relevance
“…These antimicrobials are commonly used in animal husbandry in these countries, and the increasing and inappropriate use of antimicrobials in animal farming may be the reason for these high levels of resistance [34]. MDR was observed frequently in the Salmonella isolates in this study, as shown in previous studies from Vietnam [28,34,37], China [38] and Malaysia [33]. This might lead to human infections with foodborne antimicrobial-resistant bacteria.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…These antimicrobials are commonly used in animal husbandry in these countries, and the increasing and inappropriate use of antimicrobials in animal farming may be the reason for these high levels of resistance [34]. MDR was observed frequently in the Salmonella isolates in this study, as shown in previous studies from Vietnam [28,34,37], China [38] and Malaysia [33]. This might lead to human infections with foodborne antimicrobial-resistant bacteria.…”
Section: Discussionsupporting
confidence: 73%
“…In this study, 58.7% of Salmonella isolates were resistant to at least one antimicrobial. Resistance to tetracycline, sulphonamide, ampicillin, streptomycin, trimethoprim and chloramphenicol was commonly observed in the Salmonella isolates, as shown in previous reports from Vietnam [28,34,37] and other Asia countries [33,38]. These antimicrobials are commonly used in animal husbandry in these countries, and the increasing and inappropriate use of antimicrobials in animal farming may be the reason for these high levels of resistance [34].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…M ultidrug-resistant (MDR) Salmonella enterica has increasingly emerged worldwide as a result of the extensive use of antibiotics in human and veterinary medicine (Khemtong and Chuanchuen, 2008;Ogasawara et al, 2008). Several approaches have been taken to understand the emergence and spread of antimicrobial resistance (AMR), of which monitoring and surveillance program is a key tool for tracking drug resistance, measuring its health and economic impacts, and designing targeted solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Ubeyratne et al (2008) detected Salmonella resistant to erythromycin, amoxicillin and sulfonamides in shrimp (Penaeus monodon) farmed in Sri Lanka. Likewise, Ogasawara et al (2008) found salmonelas resistant to oxytetracycline and chloramphenicol in Vietnamese shrimp samples but concluded ARI values were not as high as in neighboring or developing countries.…”
Section: Antimicrobial Susceptibility Profile Of Salmonellamentioning
confidence: 99%